2021
DOI: 10.3390/cells10113035
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of miRNAs for Muscle-Wasting Conditions

Abstract: MicroRNAs (miRNAs) are small, non-coding RNA molecules that are mainly involved in translational repression by binding to specific messenger RNAs. Recently, miRNAs have emerged as biomarkers, relevant for a multitude of pathophysiological conditions, and cells can selectively sort miRNAs into extracellular vesicles for paracrine and endocrine effects. In the overall context of muscle-wasting conditions, a multitude of miRNAs has been implied as being responsible for the typical dysregulation of anabolic and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 154 publications
(177 reference statements)
0
18
0
1
Order By: Relevance
“…miRNAs are endogenous noncoding RNAs that regulate the expression of target genes mainly at the transcriptional or posttranscriptional level and play important roles in a variety of life events. Recent studies have shown that miRNAs are involved in the regulation of MSC proliferation, lipogenesis, and osteogenic differentiation or apoptosis and play an important role in the fate determination of MSCs [ 14 , 15 ]. It has been reported [ 16 ] that miR-144-3p may be involved in the regulation of osteogenic differentiation and proliferation process of mouse MSCs.…”
Section: Prefacementioning
confidence: 99%
“…miRNAs are endogenous noncoding RNAs that regulate the expression of target genes mainly at the transcriptional or posttranscriptional level and play important roles in a variety of life events. Recent studies have shown that miRNAs are involved in the regulation of MSC proliferation, lipogenesis, and osteogenic differentiation or apoptosis and play an important role in the fate determination of MSCs [ 14 , 15 ]. It has been reported [ 16 ] that miR-144-3p may be involved in the regulation of osteogenic differentiation and proliferation process of mouse MSCs.…”
Section: Prefacementioning
confidence: 99%
“…Another hot topic of applying exosomal cargo for muscle healing is the treatment of Duchenne muscular dystrophy [ 26 , 133 , 134 ]. The transfer of SOD1 and SOD3, or myostatin propeptide through exosomes can replace the mutated SOD1, and accelerate muscle regeneration [ 26 , 133 ].…”
Section: Exosomes In Skeletal Muscle Repair and Regenerationmentioning
confidence: 99%
“…miR-147-3p, miR-299-3p, miR-1933-3p, miR-511-3p, miR-3473d, miR-665-3p, and miR-205-3p were found to be dysregulated. These miRNAs are associated with crucial cellular processes, such as cell-to-cell communication, development, growth, and inflammatory response [ 118 , 119 ]. Notably, miR-205 has been also found to be upregulated in different types of cancer, such as colorectal cancer and nasopharyngeal cancer.…”
Section: Cachexia–exclusive Mirnasmentioning
confidence: 99%
“…In adult skeletal muscle, miR-205 plays a crucial role in proteasomal degradation, thereby altering muscle proteostasis in a negative manner. Indeed, it was predicted that miR-205 targets the MYC proto-oncogene, bHLH transcription factor (MYC), thus leading to the inhibition of AKT and cascade activation of E3 ligases, atrogin-1/muscle atrophy F-box (MAFbx) and muscle RING finger 1 (MurF-1), the main mediators of muscle protein degradation in cachexia [ 110 , 119 ]. Furthermore, CREB1 is also targeted by miR-450a-5p and was found to be upregulated in skeletal muscles of cachectic non-small-cell lung carcinoma (NSCLC) patients.…”
Section: Cachexia–exclusive Mirnasmentioning
confidence: 99%